IMPACT OF DIGITAL TRANSFORMATION ON INDIA’S INFORMATION TECHNOLOGY EMPLOYEES IN RETAIL INDUSTRY - FROM LEARNING PERSPECTIVE - Paul, Aparesh (Digital Repository of Theses, 2023)
Digital Transformation is driving significant changes in the industries, including the retail industry. As organizations adopt new emerging technologies to meet customers’ expectations and improve performance, Information Technology (IT) employees play a crucial role in supporting these efforts. However, while IT organizations create a learning environment to reskill employees with emerging technologies, some employees quickly learn and adapt to the emerging technologies, others face challenges in keeping up with the pace of change. This research focuses on the impact of digital transformation on IT employees in the retail industry in India. The study aims to understand the challenges employees face in learning new technologies and their experience of performance improvement resulting from adopting these technologies. The research highlights common challenges related to time management, interruptions and the complexity of technologies. The findings of this study can provide valuable insights to IT leaders, enabling them to better understand the impact of digital transformation on IT employees and develop frameworks to address challenges and enhance the learning process. By fostering a smoother learning experience and improving employee productivity, organizations can accelerate their digital transformation efforts and overall growth.